Extraction, characterization and evaluation of Eruca sativa against streptozotocin-induced diabetic nephropathy in rat (Bangladesh Journal of Pharmacology, 2017)
The present study was aimed to evaluate petroleum ether and hydroalcohol extracts of Eruca sativa seeds in the treatment of diabetic nephropathy in the rat model. GC-MS analysis of petroleum ether extract revealed the presence of fatty acids and erucic acid. Quercetin and kaempferol were isolated from the hydroalcohol extract. Diabetes was induced in rat by streptozotocin (65 mg/kg i.p.) 15 min after nicotinamide (230 mg/kg, i.p.) administration. Both the extracts at different doses produced a significant attenuation in the elevated serum glucose level. Elevated renal parameters, lipid and anti-oxidant enzyme levels were restored in a dose-dependant manner. Moreover, both extracts produced significant reduction in the formation of advanced glycation end products in the kidney. These findings suggest that E. sativa might inhibit the progression of diabetic nephropathy and could be a therapeutic agent for the management of diabetic nephropathy.Video Clip of Methodology:Extraction of compounds from seeds: 3 min 45 sec   Full Screen   Alternate